West syndrome and mosaic trisomy 13: A case report - Hechmi Ben Hamouda; Habib Soua; Mohamed Dogui; Hassine Hamza; Mohamed Tahar Sfar (Paediatrica Indonesiana, 2018)
Trisomy 13, or Patau syndrome, is a rare chromosomal disorder characterized by a triad of cleft lip and palate, postaxial polydactyly, and microphthalmia, with an incidence ranging between 1/5,000 and 1/20,000 births.1 Most patients (80%) with Patau syndrome have complete trisomy 13. Mosaic trisomy 13 is very rare; it occurs in only 5% of all patients with the trisomy 13 phenotype.2 Trisomy 13 is a clinically severe entity, and 90 to 95% of patients born with this syndrome do not survive beyond one year of life. However, patients with mosaic trisomy 13 usually have longer survival and less severe phenotype compared to patients with complete trisomy 13. Malformations mainly affect midline development, with a high frequency of central nervous system involvement. The presence of central nervous system malformations is important as a predictive factor of survival.1,3 It is well known that the incidence of epilepsy is higher in children with Patau syndrome than in the general population, and West syndrome or infantile spasms have been rarely reported in these children.1,4,5 Prior to our report, there has been no case report of West syndrome associated with mosaic trisomy 13. The association of West syndrome with trisomy 13 is considered a symptomatic West syndrome because of preexisting psychomotor development delay and the poor prognosis in most of these children.6 We report here the first case of West syndrome in a girl with mosaic trisomy 13 and discuss the clinical characteristics and prognosis of this association.